Artificial intelligence - Rich, Elaine (McGraw-Hill, 1991)
The book develops the theory and practice of heuristic search, providing detailed algorithms for standard search method. It also explores a variety of methods for encoding knowledge in computer systems. There are also chapters on both symbolic and numeric techniques for reasoning under uncertainty.